Revision of the Patagonian stiletto fly genus Pachyrrhiza Philippi (Therevidae: Agapophytinae) - Irwin, Michael E.; Winterton, Shaun L. (Zootaxa, 2021)
In South America, the stiletto fly subfamily Agapophytinae (Diptera: Therevidae) occurs predominantly in the Patagonian region where it is represented by four genera: Pachyrrhiza Philippi, Melanothereva Malloch, Entesia Oldroyd and Sigalopella Irwin & Winterton. Here we revise the genus Pachyrrhiza with an additional four new species described and figured.